Bias Gender dalam Buku Teks Pendidikan Agama Islam dan Kristen - Murfi, Ali (Jurnal Pendidikan Islam, 2014)
This research has been done to reveal the gender bias in text books of Islamic and Christian religious educationas as the basis for promoting gender concept religious education factually. These findings show that the text books of Islamic and Christian religious, which are learnt by students nowadays, are found only a little value of gender norm. Because of this, it is necessary for the religious education lessons are to be revised and implemented the comprehension of gender bias by professional teacher. This is as the innovative movement of religious education about equality and equity of women and men in the access of economic, social, cultural and political activities.